2002
DOI: 10.1123/apaq.19.3.300
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Children with Physical Disabilities on Inclusion and Empowerment: Supporting and Limiting Factors

Abstract: The purpose was to explore the personal experiences of children with physical disabilities in physical education (PE) and to identify supporting and limiting mechanisms to their inclusion and empowerment. A computerized analysis of individual profiles was performed based on in-depth interviews with 8 females and 2 males, ages 9 to 15, who were included in regular PE classes. Two individual profiles served as examples for situations faced during inclusive settings and typical reaction patterns. A comparative qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
37

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 32 publications
2
62
0
37
Order By: Relevance
“…Indeed, the athletes consistently pinpointed how these relationships had enriched their sport experiences in each of the outcome themes. This finding lends support to the contention that social interactions can play a central role in facilitating positive experiences (Hutzler et al, 2002;Spencer-Cavaliere & Watkinson, 2010).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Indeed, the athletes consistently pinpointed how these relationships had enriched their sport experiences in each of the outcome themes. This finding lends support to the contention that social interactions can play a central role in facilitating positive experiences (Hutzler et al, 2002;Spencer-Cavaliere & Watkinson, 2010).…”
Section: Discussionsupporting
confidence: 59%
“…Results indicated that athletes' sport enjoyment and perceptions of physical ability were strongly related to youth's desire to continue participating in sport, thereby suggesting that youth's individual perceptions may play a key role in facilitating positive outcomes. Hutzler, Fliess, Chacham, and Van den Auweele (2002) echoed this sentiment as their investigation revealed that the self-efficacy and goal perspectives of students with disabilities influenced their perceptions of empowerment. Moreover, Hutzler and colleagues (2002) found that external factors, such as peers and important adults, also fostered empowerment within inclusive physical education.…”
Section: Introductionmentioning
confidence: 95%
“…being taught in another locality by other non-PE staff) or limited inclusion (for example, being positioned as an observer or passive participant such as a referee) are common practices (Blinde and McAllister 1998;Goodwin and Watkinson 2000;Smith 2009). Secondly, and often as the result of the latter, too many young people with disabilities experience being made to feel like 'outsiders' or 'incompetent' by peers, or are teased in PE lessons (Doubt and McCall 2003;Fitzgerald 2005;Hutzler et al 2002;Smith 2009). Thirdly, PE teachers are also reported to make young disabled students feel marginalised because they appear to lack the knowledge or lack the confidence to adapt teaching and learning tasks in their lessons, and do little to encourage their active participation (Blinde and McAllister 1998;Doubt and McCall 2003;Fitzgerald 2005;Goodwin 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, teachers reported to propose activities only for student's fun and enjoyment. The limited participation of student with a disability in physical education classes has been described by several other authors (ALVES;DUARTE, 2013;BLINDE;MCCALLISTER, 1998, GOODWIN, 2001WATKINSON, 2000, HUTZLER et al, 2002PLACE;HODGE, 2001) as well as activities without educational purposes (FALKENBACH et al 2007;RODRIGUES;FERREIRA, 2013), demonstrating how challenging it is to promote inclusion in schools.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have shown that students with disability associate physical education classes with negative experiences (BREDAHL, 2013), feeling excluded, experiencing limited participation, and even being totally segregated from their peers (ALVES; DUARTE, 2013;BLINDE;MCCALLISTER, 1998;MENDES;SÁ, 2011;WATKINSON, 2000;HAEGELE;SUTHERLAND, 2015;HUTZLER et al, 2002;FRANK et al, 2013;PLACE;HODGE, 2001;RODRIGUES;FERREIRA, 2013;FALKENBACH et al, 2007). Chicon, Mendes and Sá (2011) even described a case in which students with disability were excluded from general physical education classes and had to practice different activities without any clear educational meaning.…”
Section: Introductionmentioning
confidence: 99%